Regulation of IFNβ expression: focusing on the role of its promoter and transcription regulators - Fan, Jiqiang; Li, Qiumei; Liang, Jiadi; Chen, Zhirong; Chen, Linqin; Lai, Junzhong; Chen, Qi (Frontiers in Microbiology, 2023)
IFNβ is a single-copy gene without an intron. Under normal circumstances, it shows low or no expression in cells. It is upregulated only when the body needs it or is stimulated. Stimuli bind to the pattern recognition receptors (PRRs) and pass via various signaling pathways to several basic transcriptional regulators, such as IRFs, NF-кB, and AP-1. Subsequently, the transcriptional regulators enter the nucleus and bind to regulatory elements of the IFNβ promoter. After various modifications, the position of the nucleosome is altered and the complex is assembled to activate the IFNβ expression. However, IFNβ regulation involves a complex network. For the study of immunity and diseases, it is important to understand how transcription factors bind to regulatory elements through specific forms, which elements in cells are involved in regulation, what regulation occurs during the assembly of enhancers and transcription complexes, and the possible regulatory mechanisms after transcription. Thus, this review focuses on the various regulatory mechanisms and elements involved in the activation of IFNβ expression. In addition, we discuss the impact of this regulation in biology.